Evaluation of Urine Dipstick For Leukocyte Esterase Test For Diagnosis of Urinary Tract Infection - Rahem Al-Salihy, Shaima'a (Diyala Journal of Medicine, 2020)
Background:General urine examination (GUE) and urine culture are the most requested tests by clinicians for patients with symptoms suggestive of urinary tract infections (UTI). However, they are laborious methods. So dipstick probably become rapid diagnostic alternative. Objective: To determine the sensitivity, specificity, positive and negative predictive values of dipstick for leukocyte esterase (LE) test compared with gold standard urine culture for diagnosis of UTI. Patients and Methods: A total of 150 mid-stream urine samples were collected from adult patient with clinically diagnosed or suspected UTI, during the period from 1st September to 1st December, 2018. Urine culture, general urine examination (GUE) and dipstick for LE were performed for each sample. Results: In the 150 urine samples, 126 (84%) were culture positive, and the prevalence of UTI among female (84.13%) was significantly higher than the prevalence among males (15.87%). Approximately, half of urine culture grew E.coli 70 (46.67%) followed by Klebsiella spp. 55 (36.67%), and Staphylococcus aureus 1(0.67%). The sensitivity, specificity, positive and negative predictive values of dipstick for LE test were 86.5%, 87.5%, 97.3% and 55.25%, respectively. However, the values can be enhanced by combination with GUE. Conclusion: Both general urine examination (GUE) and dipstick for leukocyte esterase (LE) methods are with predictive value in diagnosis of UTI. Because urine culture is an expensive and delayed test, rapid test could be a good substitution to reduce the workload and a good screening method.